Incidental detection of ectopic liver tissue during elective cholecystectomy: a case report - Emral, Ahmet Cihangir (Frontiers in Surgery, 2025)
IntroductionEctopic liver tissue (ELT) is a rare embryological anomaly most commonly found in the abdominal region, particularly on the gallbladder. It is generally asymptomatic and is often discovered incidentally during surgery or autopsy. Although histologically similar to the main liver, ELT should be excised due to the potential risk of malignancy.Case presentationThis study presents a case of incidental ELT discovered during elective cholecystectomy in a 34-year-old female patient. Preoperative imaging revealed multiple gallstones, and during laparoscopic exploration, an ectopic liver tissue lesion was found on the gallbladder fundus. The lesion, measuring 10 × 5 mm, was excised en bloc with the gallbladder and sent for pathological examination, which showed no malignancy.DiscussionThe rarity and asymptomatic nature of ELT make it difficult to diagnose preoperatively, but its association with malignant transformation warrants careful management. In cases of suspected malignancy, further surgical approaches such as extended surgical margins and regional lymph node dissection should be considered.ConclusionThis case underscores the importance of early detection and excision of ectopic liver tissue due to its potential for malignant transformation.